DABIGATRAN AND IDARUZIZUMAB. NEW OPPORTUNITIES FOR IMPROVING PATIENT SAFETY - N. A. Novikova; A. N. Volovchenko; D. A. Parfenov («REMEDIUM GROUP» Ltd., 2019)
The widespread use of new oral anticoagulants in clinical practice requires improving the safety of medication use, i.e. the use of specific reversal agents, if necessary. Idarucizumab, a humanied monoclonal antibody fragment, is the first reversal agent authorized in our country that binds to dabigatran. Its efficacy and safety have been validated in several clinical trials, and its use gains experience in real clinical practice.